Polar patrol balloon I. Balloon System - Jun Nishimura; Masahiro Kodama; Koichiro Tsuruda; Hiroshi Fukunishi (National Institute of Polar Research, 1984)
Because of the importance of the balloon observations in the polar region, a project, Polar Patrol Balloon, is proposed in which a balloon will be able to float and observe around Antarctica for a month. In this project, the balloons are to be launched from some bases in Antarctica where there is no sunrise in the winter and no sunset in the summer, and a zero pressure balloon can maintain its altitude for one month by dropping a small amount of ballast. A study of meteorological feasibility had been made for this project, and it was found that a period for the balloon to fly around the pole is about one week in the winter and a few weeks in the summer at an altitude of 30km. The deviation of the trajectory from a circle is smaller in the summer season. A feasibility study was also made for power supply, on board memory storing observed data, and auto-ballasting system to perform the flight of about one month. The balloon will be located by ARGOS systems during the flights. Some merits of possible international collaboration for this project are also discussed